Structural characterization of an arboreal community of a silvopastoral system in a floristic transition area of Nuevo Leon - Canizales-Velázquez, Pamela Anabel; Aguirre-Calderón, Óscar Alberto; Alanís-Rodríguez, Eduardo; Rubio-Camacho, Ernesto; Mora-Olivo, Arturo (Instituto de Ecología, A.C., 2019)
The arboreal communities of a silvopastoral agroecosystem play an important role in the arid and semiarid ecosystems of the country, by conserving the biodiversity and the development of the livestock activities that are of vital importance in the North of Mexico. With the objective of characterizing an arboreal community of a silvopastoral agroforestry system in a transition zone of tamaulipan thornscrub and mezquital in Nuevo Leon, five sampling sites of 2500 m2 were established; we made an inventory of all tree species with diameter at the height of 1.30 m (DBH) > 7.5 cm. The vertical and horizontal structure and composition were evaluated through vegetation analysis (relative abundance, relative frequency, relative dominance), importance value index, forest value index and models for the variables normal diameter – canopy cover. The main species from an ecological standpoint were Prosopis laevigata (Hump. & Bonlp., Ex.Will.) M. C. Johnst. and Ebenopsis ebano (Berland.) Barneby & J. W. Grimes, the community presented high density of individuals, high canopy cover and a vertical structure with a high proportion of individuals ≥6 m in height. The linear model showed the best adjustments by presenting an R2 = 0.621. Silvopastoral management has conserved and promoted the structural attributes of the native plant community.